m6A Methylation Analysis of Differentially Expressed Genes in Skin Tissues of Coarse and Fine Type Liaoning Cashmere Goats - Wang, Yanru; Zheng, Yuanyuan; Guo, Dan; Zhang, Xinghui; Guo, Suling; Hui, Taiyu; Yue, Chang; Sun, Jiaming; Guo, Suping; Bai, Zhixian; Cai, Weidong; Zhang, Xinjiang; et al. (Frontiers in Genetics, 2020)
N6-methyladenosine (m6A) is the most common internal modification in mRNAs of all higher eukaryotes. Here we perform two high-throughput sequencing method, m6A-modified RNA immunopreciplation sequence (MeRIP-seq) and RNA sequence (RNA-seq) to identify key genes with m6A modification in cashmere fiber growth. Total of 9085 m6A peaks were differentially expressed as defined by MeRIP-seq, including 7170 upregulated and 1915 downregulated. In addition, by comparing m6A-modified genes between the fine-type Liaoning cashmere goat (FT-LCG) and corse-type Liaoning cashmere goat (CT-LCG) skin samples, we obtain 1170 differentially expressed m6A-modified genes. In order to identify the m6A-modified genes related to cashmere fiber growth, 19 genes were selected to validate by performing qRT-PCR in FT-LCG and CT-LCG. In addition, GO enrichment analysis shows that differentially expressed m6A-modified genes are mainly involved in keratin filament and intermediate filament. These findings provide a theoretical basis for future research on the function of m6A modification during the growth of cashmere fiber.